The Influence of Career Development and Salaries on Employee Loyalty at the New Hollywood Hotel Pekanbaru - Perangin-angin, Febriani br; Karneli, Okta (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
This research was conducted at the New Hollywood Hotel Pekanbaru. The purpose of this study was to determine the effect of career development and salary provision on employee loyalty. Career development and salary provision as independent variables (X1,X2) while employee loyalty as the dependent variable(Y). The problem in this research is the decline in employee loyalty at Hotel New Hollywood Pekanbaru. This can be seen from the company attendance data. The sample of this research was taken as many as 55 respondents from the population calculated using the census/total sampling technique. The data obtained from the questionnaire results and then processed to then be tested with statistics through the SPSS program. The analysis technique uses the regression equation, the coefficient of determination (R2) test, and hypothesis testing, namely the partial test (t test) and simultaneous test (f test). The results of test carried out show that career development and salary provision have a positive and significant effect on employee loyalty at the New Hollywood Hotel Pekanbaru.